Motivating the SEL field forward through equity - Yoder, Nicholas; Skoog-Hoffman, Alexandra (Advances in motivation and achievement, 2021)
How do we navigate uncertain times? What competencies and motivational factors accelerate us to grow and develop and what hinders our success? What are strategies that researchers, educators and policymakers can engage in to more fully realize the potential of all students, combatting institutional and interpersonal inequities? To answer these questions, we need to develop a deeper understanding of what motivates youth and adults, inclusive of the contextual and institutional variables that influence individuals, to develop and apply their social and emotional competencies. Motivating the SEL Field Forward Through Equity looks for a deeper critical understanding of the role of social and emotional learning (SEL) as a lever for equitable access to the competencies and skills individuals will ultimately need to be successful in school, work, and life. To do this, we need to explore the motivational factors of individuals and how that connects to SEL for all students, programs and practices that promote a more equitable SEL experience for all students, and practices to engage researchers and practitioners to deepen implementation of SEL with all students. This handbook will benefit the broader SEL market including researchers, practitioners, school and district leaders, and teacher preparation programs in the SEL and motivation fields who are actively engaged in working to create equitable outcomes for adults and youth.